Sn-doped high-voltage lithium nickel manganese oxide positive electrode material as well as preparation method and application thereof
The Sn-doped high-voltage lithium nickel manganate positive electrode material was prepared by one-step spray drying, which solved the problems of poor structural stability and poor circulation performance of LNMO materials, and achieved battery performance with high specific capacity and good circulation stability.
Patent Information
- Application Number
- CN202411380699.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-09-30
AI Technical Summary
LiNi0.5Mn1.5O4 (LNMO) positive electrode material has poor structural stability during charging and discharging, resulting in poor cycling performance and transition metal Mn is easily dissolved, affecting battery performance.
A Sn-doped high-voltage lithium nickel manganate positive electrode material was prepared by one-step spray drying. The process conditions were controlled to obtain materials with excellent lithium ion and electron conduction properties through acetate and citric acid as raw materials and complexing agents.
It improves the structural stability and cyclic stability of the material, enhances the lithium ion conduction and electron conduction properties, shows high specific capacity and good cyclic performance, and is suitable for the positive electrode materials of lithium ion batteries.
Smart Images

Figure CN119461512A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery positive electrode materials, and in particular relates to a Sn-doped high-voltage lithium nickel manganese oxide positive electrode material and a preparation method and application thereof. Background Art
[0002] LiNi 0.5 Mn 1.5 As a high-voltage cathode material, O4 (LNMO) has attracted much attention in the field of lithium-ion batteries due to its high energy density, high operating voltage, low cost and environmental friendliness. LNMO has an operating voltage of up to 4.7V and an energy density of up to 650Wh / kg, making it an ideal choice for improving battery energy density.
[0003] Moreover, LNMO has three-dimensional lithium ion diffusion channels, which form fast ion diffusion kinetics, making Li + It has a faster ion migration speed in the electrolyte and at the interface between the electrolyte and the electrode. However, the structural stability of LNMO deteriorates due to the two-phase transition during the charge and discharge process, resulting in poor cycle performance. In addition, during the cycle of LNMO, the transition metal (Mn) is easily dissolved from the lattice and transferred to the electrolyte, resulting in the collapse of the spinel structure of the LNMO electrode and the increase of the charge transfer impedance, thereby seriously deteriorating the battery performance. Moreover, the Jahn-Teller effect in the Mn-O framework will cause the LNMO positive electrode structure to be distorted, which is easy to cause structural degradation and lead to rapid capacity decay. Therefore, for LNMO positive electrode materials, high structural stability and optimized electrochemical performance are key requirements for achieving high energy density lithium-ion battery energy storage.
[0004] The structural basis of LNMO includes two different polymorphs: a cationic ordered phase (space group P4332, called o-LNMO) and a cationic disordered phase (space group Fd-3m, called d-LNMO). These structures differ at the atomic scale, and these differences affect the electrochemical properties of the material; the difference in electrochemical performance between o-LNMO and d-LNMO is mainly reflected in rate performance and cycle stability. The ordered phase o-LNMO has good structural stability and low activation energy for lithium ion migration, which is theoretically beneficial to improving the conductivity and ion diffusion coefficient of the material. However, it is found in practical applications that d-LNMO, due to its disordered structure, may be more conducive to the transport of lithium ions and show better rate performance. Therefore, the current synthesis of LNMO is mainly based on the synthesis of disordered phase LNMO. In order to improve the performance of LNMO, researchers have adopted a variety of strategies, such as optimizing the material structure through bulk doping, coating, morphology control, etc.
[0005] Through in-situ doping, trace elements can be effectively incorporated into specific sites of the LNMO lattice to stabilize the lattice and prevent structural collapse, which is very effective. At present, the solid-phase method is mostly used for doping, but the solid-phase method usually involves mechanical mixing of lithium source, manganese source and nickel source and high-temperature calcination, which may cause uneven mixing of raw materials, thereby affecting electrochemical performance. Moreover, the materials synthesized using the solid-phase method often have irregular morphology, which may affect the conductivity and ion diffusion properties of the material. Summary of the invention
[0006] The object of the present invention is to provide a Sn-doped high-voltage lithium nickel manganese oxide positive electrode material and a preparation method and application thereof. The preparation process is simple to operate, and the raw materials are cheap and easily available. The obtained positive electrode material is used as a positive electrode active material for lithium ion batteries and has excellent lithium ion conduction and electron conduction properties, and exhibits high specific capacity and cycle stability.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0008] A method for preparing a Sn-doped high-voltage lithium nickel manganese oxide positive electrode material is provided, comprising the following steps:
[0009] 1) dissolving a lithium source, a nickel source, a manganese source and a tin source in water, wherein the lithium source, the nickel source, the manganese source and the tin source are all acetates, and then adding a complexing agent, citric acid, and stirring to react;
[0010] 2) drying and spraying the mixed solution obtained in step 1) to obtain a solid powder;
[0011] 3) Pre-sintering, grinding, re-sintering and grinding the solid powder obtained in step 2) to obtain Sn-doped high-voltage lithium nickel manganese oxide positive electrode material.
[0012] According to the above scheme, in step 1), the lithium source, nickel source, manganese source and tin source are in the chemical formula LiNi 0.5 Mn 1.5-x Sn x O4 is fed in a stoichiometric ratio, where x is 0.035 to 0.045.
[0013] Preferably, the lithium source is in excess of 4-6%, and a slight excess of lithium acetate is used to compensate for the lithium loss during the high-temperature sintering process.
[0014] According to the above scheme, in step 1), the molar volume ratio of the nickel source to water is 0.005 mol: 150 mL to 200 mL.
[0015] According to the above scheme, in step 1), the molar ratio of citric acid to transition metal ions is 0.8 to 1:1, wherein the transition metal is Ni, Mn and Sn.
[0016] According to the above scheme, in step 1), the stirring reaction time is 12 to 18 hours.
[0017] According to the above scheme, in step 2), the spray drying outlet temperature is set to 190-210°C.
[0018] According to the above scheme, in step 3), the pre-sintering process is: pre-sintering at 500℃~600℃ for 4h~6h; preferably, the heating rate is 3~5℃min -1 .
[0019] According to the above scheme, in step 3), the grinding time after pre-sintering is 1 to 1.5 hours.
[0020] According to the above scheme, in step 3), the sintering process is: sintering at 800-900°C for 8-10h; preferably, the heating rate is 3-5°C min -1 .
[0021] According to the above scheme, in step 3), the grinding time after sintering is 1 to 1.5 hours.
[0022] Through pre-sintering and sintering conditions, the particle size distribution and morphology of LNMO materials can be adjusted, and the structural and interfacial chemical stability of the materials as well as the interfacial charge transfer kinetics can be significantly improved.
[0023] Provided is a Sn-doped high-voltage lithium nickel manganese oxide positive electrode material prepared by the above method, which has a truncated octahedral crystal morphology and a three-dimensional lithium ion diffusion channel.
[0024] Provided is an application of the Sn-doped high-voltage lithium nickel manganese oxide positive electrode material in a lithium ion battery.
[0025] Provided is a lithium-ion battery comprising the Sn-doped high-voltage lithium nickel manganese oxide positive electrode material.
[0026] The present invention provides a method for preparing Sn-doped high-voltage lithium nickel manganese oxide positive electrode material, which adopts a one-step spray drying technology to achieve direct conversion from solution to dry product, significantly simplifying the preparation process and improving production efficiency. Through this technology, the lithium source can penetrate deeply into the interior of the precursor particles, avoiding the subsequent lithium doping step, and ensuring the uniformity and consistency of the material. In addition, the one-step spray drying method achieves uniform mixing of the raw materials at the molecular level by atomizing the raw material droplets into fine droplets, improves the uniformity of the material, and enhances its compaction density and ion transport performance. The method also allows the physical conditions during the drying process to be precisely controlled, thereby preparing particles with a specific morphology, ensuring the precise control of the stoichiometric ratio of the precursor, and achieving the desired chemical composition and structure.
[0027] The present invention selects metal acetate and utilizes its high solubility to prepare a precursor solution with a high solid content, reduce the evaporation of the solvent during the spray drying process, and improve the drying efficiency; at the same time, the acetate can form a uniform complex in the solution, which is conducive to forming uniform droplets during the spray drying process, thereby preparing a positive electrode material with uniform particle size distribution. In addition, the use of acetate raw materials can reduce the introduction of other ions, such as SO4 2- or Cl - Etc., avoiding the negative impact of impurity ions on battery performance.
[0028] The present invention selects citric acid as a complexing agent. On the one hand, citric acid is a multi-dentate chelating agent that can form a stable chelate with multiple metal ions, which helps to ensure the uniform distribution of metal ions (such as nickel, manganese, etc.) in the solution, thereby forming uniform precursor particles during the spray drying process, and then helping to obtain a positive electrode material with a uniform chemical composition. On the other hand, citric acid can affect the crystallization process of the precursor, help to form a positive electrode material with a specific morphology and particle size distribution, and reduce the introduction of other impurity ions, which has a positive effect on the electrochemical performance of the battery. At the same time, citric acid is relatively stable during the heating process and is not prone to decomposition, which helps to maintain the uniformity of the solution during the spray drying process, thereby obtaining a uniform positive electrode material. In the subsequent heat treatment process, the gas produced by the decomposition of citric acid can help remove moisture and other volatile impurities in the material and improve the purity of the material.
[0029] The beneficial effects of the present invention are as follows:
[0030] 1. The present invention provides a method for preparing a Sn-doped high-voltage lithium nickel manganese oxide positive electrode material. The Sn-doped high-voltage lithium nickel manganese oxide positive electrode material is prepared by a one-step spray drying method using a lithium source, a nickel source, a manganese source and a tin source in the form of acetate as raw materials, selecting citric acid as a complexing agent; the obtained high-voltage lithium nickel manganese oxide positive electrode material has high purity, excellent uniform particle size and good truncated octahedral crystal structure, Sn doping effectively improves structural stability, has excellent lithium ion conduction and electronic conduction performance, and exhibits high specific capacity and cycle stability, wherein at 100 mA g -1 At a current density of 1.34 W, it has a high reversible charge-discharge capacity (110.69 mAh g -1 ), after 350 cycles, the charge-discharge capacity remained at 102.64 mAh g -1 It has important application prospects.
[0031] 2. The preparation process of the present invention is simple to operate, has few steps, high production efficiency, and the raw materials are cheap and readily available, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 11 is the XRD diagram of the Sn-doped high-voltage lithium nickel manganese oxide positive electrode material of Example 1 of the present invention.
[0033] Figure 2 This is a Raman graph of the Sn-doped high-voltage lithium nickel manganese oxide positive electrode material of Example 1 of the present invention.
[0034] Figure 3 This is a SEM image of the Sn-doped high-voltage lithium nickel manganese oxide positive electrode material of Example 1 of the present invention.
[0035] Figure 4 This is a CV diagram of the Sn-doped high-voltage lithium nickel manganese oxide positive electrode material of Example 1 of the present invention.
[0036] Figure 5 This is a voltage distribution diagram of the Sn-doped high-voltage lithium nickel manganese oxide positive electrode material of Example 1 of the present invention.
[0037] Figure 6 This is a cycle performance diagram of the Sn-doped high-voltage lithium nickel manganese oxide positive electrode material of Example 1 of the present invention.
[0038] Figure 7 This is an EIS impedance diagram of the Sn-doped high-voltage lithium nickel manganese oxide positive electrode material of Example 1 of the present invention. DETAILED DESCRIPTION
[0039] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0040] Embodiment 1:
[0041] The method for preparing Sn-doped high-voltage lithium nickel manganese oxide positive electrode material comprises the following steps:
[0042] 1) 0.0105 mol CH3COOLi, 0.005 mol (CH3COO)2Ni·4H2O, 0.0146 mol (CH3COO)2Mn·4H2O and 0.0004 mol (CH3COO)2Sn were mixed and completely dissolved in 150 mL deionized water, and then 0.02 mol citric acid was added and dissolved in deionized water as a complexing agent, and magnetic stirring was performed for 12 h;
[0043] 2) setting the outlet temperature to 190° C., atomizing the solution stirred evenly in step 1) and drying it in a spray dryer under dry hot air conditions;
[0044] 3) The powder obtained in step 2) was placed in a muffle furnace at 5°C min -1 The heating rate was heated to 500℃ and pre-sintered for 4h;
[0045] 4) taking out the pre-sintered powder from step 3) and grinding it in a mortar for 1 h;
[0046] 5) Place the powder ground in step 4) in a muffle furnace at 5°C min -1 The temperature was raised to 800℃ and calcined for 10h.
[0047] 6) After the temperature drops naturally, the sample obtained in step 5) is taken out and ground for 1 hour, and finally a Sn-doped high-voltage lithium nickel manganese oxide positive electrode material sample is obtained.
[0048] The Sn-doped high-voltage lithium nickel manganese oxide positive electrode material sample obtained in this embodiment is tested as follows:
[0049] like Figure 1 As shown, the X-ray diffraction (XRD) spectrum of the Sn-doped high-voltage lithium nickel manganese oxide positive electrode material determined by an X-ray diffractometer shows that after high-temperature calcination, the materials all have a spinel structure with Fd-3m space group symmetry, and the characteristic peaks of the Sn-doped high-voltage lithium nickel manganese oxide positive electrode material are obvious. There are trace diffraction peaks of SnO in the XRD spectrum, which does not affect the integrity of the LNMO crystal structure.
[0050] like Figure 2 As shown, through Raman spectroscopy analysis (Raman) of Sn-doped high-voltage lithium nickel manganese oxide positive electrode materials: commercial red phosphorus at 400cm -1 -700cm -1 There are three characteristic peaks between the ranges, located at 493 cm -1 、599cm -1 and 633cm -1 It is consistent with the standard Raman spectrum of disordered Fd-3m space group LNMO, which indicates that the synthesized Sn-doped high-voltage lithium nickel manganese oxide positive electrode material has a spinel structure with Fd-3m space group symmetry.
[0051] like Figure 3 As shown in the figure, through scanning electron microscope (SEM) imaging, it can be seen that after high-temperature sintering, the Sn-4 sample presents a truncated octahedron morphology and its sample surface is not smooth. It can be clearly found that the sample surface is coated with particles, which is due to the surface coating SnO enriched on the surface. The truncated LNMO octahedron can significantly inhibit the side reaction of the electrode / electrolyte interface under high cut-off voltage and improve the cycle stability of LNMO high-voltage positive electrode materials.
[0052] The Sn-doped high-voltage lithium nickel manganese oxide material prepared by the invention is used as a positive electrode active material for lithium-ion batteries. The Sn-doped high-voltage lithium nickel manganese oxide material prepared in Example 1 is used as a positive electrode, metallic lithium is used as a counter electrode, 1M EC:DEC=1:1 (vol%) electrolyte is selected, Celgard 2400 polypropylene film is used as a separator, and CR2016 stainless steel is used as a battery shell to assemble into a button-type half-cell. Figure 5 As shown in the figure, the Sn-doped high voltage lithium nickel manganese oxide material electrode has a scanning rate of 0.1 mV s -1 In the CV test, three reversible peaks appeared during the charging process, which were located at 4.05V, 4.76V and 4.83V, representing Mn 3+ To Mn 4+、 Ni 2+ / Ni 3+ and Ni 3+ / Ni 4+ The conversion corresponds to the gradual lithiation of the positive electrode. During the discharge stage, the three peaks located at 4.65, 4.6 V, and 4.0 V show the gradual delithiation process. The almost overlapping cathode CV curves indicate that the Sn-doped cathode has good cycling stability.
[0053] like Figure 5 As shown in the figure, Sn-doped high voltage lithium nickel manganese oxide electrode material is -1 The charge-discharge voltage distribution diagram under the current density and 3.5-4.9V voltage window conditions shows that the voltage platform that appears during the charge-discharge process is consistent with the redox behavior scanned during the CV process; the first charge capacity of the Sn-doped high-voltage lithium nickel manganese oxide electrode material is 133.52mA hg -1 , the discharge capacity is 110.69mA hg -1 , the Coulombic efficiency is 82.91%. In the subsequent cycle process, the voltage platform overlaps, indicating that Li + Good reversibility of deintercalation.
[0054] like Figure 6 As shown in the figure, Sn-doped high voltage lithium nickel manganese oxide electrode material is -1 At the current density, the initial charge capacity is 110.69 mA h g -1 After 350 cycles, the charge-discharge capacity remained at 102.64 mA hg -1 Sn doping can alleviate the two-phase phase transition of LNMO materials during high-voltage cycling, effectively reduce the dissolution of Mn, prevent the structure from undergoing an unfavorable two-phase reaction to form a rock salt phase, block the diffusion channel of lithium ions, inhibit the violent side reactions between the electrode and the electrolyte under high voltage, and improve the cycling performance of the electrode material.
[0055] like Figure 7 As shown, the EIS impedance diagram of the Sn-doped high-voltage lithium nickel manganese oxide electrode material shows that the Sn-doped high-voltage lithium nickel manganese oxide electrode material has excellent lithium ion conduction and electron conduction properties, showing good electrical conductivity of the material.
[0056] The above test results show that Sn-doped high-voltage lithium nickel manganese oxide electrode material has excellent electrochemical properties and is a potential high-performance lithium-ion battery positive electrode material.
[0057] Comparative Example 1:
[0058] 1) 0.0105 mol CH3COOLi, 0.005 mol (CH3COO)2Ni·4H2O and 0.015 mol (CH3COO)2Mn·4H2O were mixed and completely dissolved in 150 mL of deionized water, followed by adding 0.02 mol of citric acid dissolved in deionized water as a complexing agent and stirring magnetically for 12 h;
[0059] 2) setting the outlet temperature to 190°C, atomizing the stirred solution and drying it in a spray dryer under dry hot air conditions;
[0060] 3) Place the obtained powder in a muffle furnace at 5°C min -1 The heating rate was heated to 500℃ and pre-sintered for 4h;
[0061] 4) Take out the calcined powder and grind it in a mortar for 1 hour;
[0062] 5) Place the ground powder in a muffle furnace at 5°C min -1 The temperature was raised to 800℃ and calcined for 10h.
[0063] 6) After cooling naturally, the sample is taken out and ground for 1 hour to finally obtain a lithium nickel manganese oxide positive electrode material sample.
[0064] Taking the nickel manganese oxide positive electrode material obtained in this embodiment as an example, at 100 mA g -1 At the current density, the first charge capacity can reach 131.51mAh / g, the discharge capacity is 106.75mAh / g, the discharge capacity after 350 cycles is 86.91mAh / g, and the capacity retention rate is 81.4%. After analysis, it can be inferred that the undoped original LNMO material has a two-phase transition and Mn dissolution during the charge and discharge process, which leads to the collapse of the spinel structure of the LNMO electrode and the increase of charge transfer impedance, resulting in the decline of its battery capacity and cycle performance.
[0065] Comparative Example 2:
[0066] 1) 0.0105 mol CH3COOLi, 0.005 mol (CH3COO)2Ni·4H2O, 0.0148 mol (CH3COO)2Mn·4H2O and 0.0002 mol (CH3COO)2Sn were mixed and completely dissolved in 150 mL deionized water, and then 0.02 mol citric acid dissolved in deionized water was added as a complexing agent and magnetically stirred for 12 h;
[0067] 2) setting the outlet temperature to 190°C, atomizing the stirred solution and drying it in a spray dryer under dry hot air conditions;
[0068] 3) Place the obtained powder in a muffle furnace at 5°C min -1 The heating rate was heated to 500℃ and pre-sintered for 4h;
[0069] 4) Take out the calcined powder and grind it in a mortar for 1 hour;
[0070] 5) Place the ground powder in a muffle furnace at 5°C min -1 The temperature was raised to 800℃ and calcined for 10h.
[0071] 6) After the temperature drops naturally, the sample is taken out and ground for 1 hour, and finally a Sn-doped high-voltage lithium nickel manganese oxide positive electrode material sample is obtained.
[0072] Taking the nickel manganese oxide positive electrode material obtained in this embodiment as an example, at 100 mAg -1 Under the current density, the first charge capacity can reach 132.95mAh / g, the discharge capacity is 102.26mAh / g, the discharge capacity after 350 cycles is 92.03mAh / g, and the capacity retention rate is 90.1%. After analysis, it can be inferred that the LNMO material doped with 2mol% Sn has a limited supporting role due to the insufficient tin content, and the effect of avoiding the two-phase transformation and Mn dissolution during the charge and discharge process is limited, resulting in a decrease in electrochemical performance.
[0073] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.
Claims
1. A method for preparing Sn-doped high-voltage lithium nickel manganese oxide positive electrode material, characterized in that: The following steps are involved: 1) dissolving a lithium source, a nickel source, a manganese source and a tin source in water, wherein the lithium source, the nickel source, the manganese source and the tin source are all acetates, and then adding a complexing agent, citric acid, and stirring to react; 2) drying and spraying the mixed solution obtained in step 1) to obtain a solid powder; 3) Pre-sintering, grinding, re-sintering and grinding the solid powder obtained in step 2) to obtain Sn-doped high-voltage lithium nickel manganese oxide positive electrode material.
2. The preparation method according to claim 1, characterized in that: In the step 1), the lithium source, the nickel source, the manganese source and the tin source are in the chemical formula LiNi 0.5 Mn 1.5-x Sn x O4 is fed in a stoichiometric ratio, where x is 0.035 to 0.
045.
3. The preparation method according to claim 1, characterized in that: In the step 1), the molar volume ratio of the nickel source to water is 0.005 mol: 150-200 mL.
4. The preparation method according to claim 1, characterized in that: In the step 1), the molar ratio of citric acid to transition metal ions is 0.8 to 1:1, wherein the transition metals are Ni, Mn and Sn.
5. The preparation method according to claim 1, characterized in that: In the step 1), the stirring reaction time is 12 to 18 hours.
6. The preparation method according to claim 1, characterized in that: In the step 3), the pre-sintering process is: pre-sintering at 500° C. to 600° C. for 4 h to 6 h; and the sintering process is: sintering at 800° C. to 900° C. for 8 h to 10 h.
7. The preparation method according to claim 1, characterized in that: In the step 3), the grinding time after pre-sintering is 1 to 1.5 hours; the grinding time after sintering is 1 to 1.5 hours.
8. A Sn-doped high-voltage lithium nickel manganese oxide positive electrode material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the Sn-doped high-voltage lithium nickel manganese oxide positive electrode material according to claim 8 in a lithium-ion battery.
10. A lithium ion battery, characterized in that: It includes the Sn-doped high-voltage lithium nickel manganese oxide positive electrode material as described in claim 8.
Citation Information
Patent Citations
Method for synthesizing high tap density spinel material LiNi0.5Mn1.5O4
CN102344168A
Ternary positive electrode material for lithium-ion battery and preparation method of ternary positive electrode material
CN106848293A
Microwave doping preparation method of spinel type lithium nickel manganese oxide material
CN111092218A
Process for the production of lithium-manganese double oxide for lithium ion batteries and lithium-manganese double oxide for lithium ion batteries made by the sa ...
KR1020110044936A
Cited By
High-voltage LiNi0. 5Mn1. 5O4 positive electrode material constructed based on heterogeneous interface and preparation method thereof
CN122144801A